The Effect of Leadership Style and Organizational Culture on Employee Performance Through Work Motivation as an Intervening Variable at the Business Development Directorate of PT Krakatau Steel (Persero) Tbk Cilegon - Yuni Pratikno; Bambang Nurakhim; Armadhani Jati Prasetya (STMIK Dharma Wacana, 2022)
This study aims to determine the effect of leadership style and organizational culture on work motivation to improve employee performance at the Directorate of Business Development PT Krakatau Steel (Persero) Tbk Cilegon. The research was conducted using a questionnaire survey method to 60 employees as a sample. This study uses a quantitative approach with a path analysis research design. Data analysis in this study includes validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, and path analysis test. From the results of the study, it can be concluded that leadership style has a direct and significant effect on employee performance, organizational culture has a direct and significant effect on employee performance, leadership style has a direct and significant effect on work motivation, corporate culture has a direct and significant effect on work motivation, work motivation has a direct and significant effect on employee performance, leadership style has a direct and significant effect on employee performance with work motivation as an interverning variable, while organizational culture has a direct and significant effect on employee performance but is not significant through work motivation as an interverning variable.